SCHOOL LITERACY POLICY AS AN EFFORT TO STRENGTHEN 21ST-CENTURY SKILLS - Nadifa, Milatun; Zulvani, Nadia Vina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
School literacy policy is one of the education policies that aims to improve students' literacy skills. Although in line with national education goals, the survey results show that the average literacy score of Indonesian students is still far below the average of OECD countries. This study aims to analyze school literacy policies by providing an in-depth understanding of school literacy policies and their contribution to 21st-century skills development, as well as providing solutions to improve the effectiveness and equity of policy implementation. This study used a Systematic Literature Review (SLR). Literature analysis shows that school literacy policies in Indonesia have increased, reflected in the growth of school libraries, the number of books, and the participation of teachers and students in literacy activities. However, challenges such as limited access to literacy resources and lack of student motivation in reading still need to be addressed. A deep understanding of the role of school literacy policy in developing 21st-century skills can make a positive contribution to national education in Indonesia. For future research, it is recommended to explore the impact of the use of technology in improving literacy in the school environment.